Performing Scriptures: Ritualizing Written Texts in Seolwi-seolgyeong, the Korean Shamanistic Recitation of Scriptures. Issue 1 (24th June 2019) - Yoo, Yohan
Abstract : Seolwi-seolgyeong is a Korean shamanistic ritual in which shamans recite scriptures while being seated. This ritual suggests a comprehensive way of performing scriptures; scriptures are recited, written and materialized so that their sacred status is secured and their power is maximized. The recitation is the nucleus of this ritual. Though lay participants do not understand the meaning of recited scriptures, they regard the recitation as effective because the gods and evil spirits are thought to understand it. For seolwi-seolgyeong to be most efficacious, the recitation of scriptures should be supported by the materialization of scriptures. Evil spirits become frightened by reading the paper banners on which the names of gods and other words of scriptures are written. Geometric paper figures that depict gods visually scare evil spirits and those that reflect the scriptures' cosmology can hedge them in and trap them. In this ritual process, scriptures are privileged and distinguished as sacred beings in several ways. First, scriptures are ritualized when shamans and other participants in seolwi-seolgyeong treat the scriptures as no less than the words of the gods. Second, reciting the scripture is equated with the proclamation of divine words. This ritualization is considered more effective when scriptures are recited more skillfully. Third, the contents of scriptures are also ritualized when they are considered so sacred as to subdue evil spirits and heal patients and when shamans materialize the contents into paper figures on the basis of their interpretation of the cosmology and theology in scriptures.